Principles of Distributed Systems 12th International Conference, OPODIS 2008, Luxor, Egypt, December 15-18, 2008. Proceedings - Baker, Theodore P.; Bui, Alain; Tixeuil, Sebastien (Theoretical Computer Science and General Issues, 2008)
This book constitutes the refereed proceedings of the 12th International Conference on Principles of Distributed Systems, OPODIS 2008, held in Luxor, Egypt, in December 2008. The 30 full papers and 11 short papers presented were carefully reviewed and selected from 102 submissions. The conference focused on the following topics: communication and synchronization protocols; distributed algorithms and multiprocessor algorithms; distributed cooperative computing; embedded systems; fault-tolerance, reliability and availability; grid and cluster computing; location- and context-aware systems; mobile agents and autonomous robots; mobile computing and networks; peer-to-peer systems and overlay networks; complexity and lower bounds; performance analysis of distributed systems; real-time systems; security issues in distributed computing and systems; sensor networks; specification and verification of distributed systems; and testing and experimentation with distributed systems.